PENERAPAN METODE APRIORI SEBAGAI SISTEM PENDUKUNG KEPUTUSAN PEMBENTUKAN PAKET PENJUALAN BIBIT BUAH - Hammad, Rifqi; Hardita, Veny Cahya; Zulfikri, Muhammad; Sholeha, Eka Wahyu (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2022)
Taletan Ijo is an online shop that sells fruit seeds. In carrying out its business processes, he utilizes a sales information system. The system is used to manage sales data. If the data is not used, it will lead to accumulation of data but lack of information. Taletan ijo uses the manual method in its product marketing strategy so that the strategy used is not quite right. Stored sales transaction data can be used as a reference in making marketing strategies such as making product sales packages. This study uses data mining methods, namely associations with a priori algorithms to process transaction data into information that can help support decisions in determining marketing strategies. The results of the study show that the lift ratio test results obtained are 3.2 which indicates that the value is valid with a minimum number of transactions of 10 and a confidence value of 80.